Product Development Start Up Roumy (Shoes Blend Painting And Patchwork) - Abdini, Ni Gusti Ayu Arum; Gulendra, I Wayan; Budiarta, I Dewa Putu Gede (Program Studi Seni Murni ISI Bali, 2024)
Implementation of MBKM Entrepreneurship Final Project with Mitra Agung Bali Collection which is engaged in the fashion industry on the development of weaving designs for weaving feed or endek fabrics with characteristics of air brus technique and surface design. In the development of surface design, Agung Bali Collection prioritizes creativity and innovation as well as artistic skills in gold, silver, pearl and glitter colors with massage canting techniques. During the MBKM process of the Entrepreneurship Final Project, the author developed a painting shoe product with a combination of patchwork. Different old and new product stitching techniques are intended to create an impression of different aesthetic values in the shoes chosen as a medium. The marketing that the author does is based offline and online, with promotions through whatsapp, Instagram, and shopee. The types of research methods used are included in quantitative research and observation as data collection methods. The results obtained were 9 shoe products combining patchwork endek with the titles Roro, Water Waves, Ginkgo Leaves, Viewpoint, Whale, Galaxy, My Cat, Koi Place and Ladybug.